Cascade palladium-catalyzed alkenyl aminocarbonylation/ intramolecular aryl amidation: an annulative synthesis of 2-quinolones. - Tadd, A; Matsuno, A; Fielding, MR; Willis, M (2009)
Palladium-catalyzed intermolecular aminocarbonylation/intramolecular amidation cascade sequences can be used to convert a range of 2-(2-haloalkenyl)aryl halide substrates efficiently and selectively to the corresponding 2-quinolones. Delaying the introduction of the CO atmosphere allows an amination/carbonylation sequence and the preparation of an isoquinolone.